The Effectiveness of the Unplugged Informatics Approach in Improving Junior High School Students' Digital Literacy and Ethics - Uswatun Hasanah; Andi Kristanto (LPPM STKIP Kusuma Negara, 2026)
Even though the Merdeka Curriculum mandates the Social Impact of Informatics (DSI) as a vital component, many middle school students face persistent challenges in detecting online falsehoods and maintaining ethical behavior online. This investigation aimed to analyze the impact of the Informatics Unplugged strategy on enhancing digital literacy and ethical awareness among students. A quantitative quasi-experimental approach featuring a Non-equivalent Control Group Design was deployed. The participant pool comprised eighth-grade students at SMP Negeri 2 Tulangan; samples were gathered through purposive sampling, allocating one group to an experimental class utilizing Informatics Unplugged and another to a control class under conventional teaching. Data collection instruments included a validated digital literacy test and a digital ethics questionnaire. For data analysis, paired-sample t-tests, independent-sample t-tests, and normalized gain (N-Gain) metrics were applied. The empirical evidence demonstrated a statistically significant divergence between the experimental and control cohorts (p < .05). The experimental set recorded a high N-Gain of 0.74, contrasting with the control set's 0.38, which marks a superior progress in both digital literacy and ethics. Ultimately, the study confirms that the Informatics Unplugged model is highly capable of driving improvements in students' digital competence, making it an advantageous instructional alternative for teaching DSI contextually.